Racial Disparities in Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: Does Aggressive Surgical Treatment Overcome Cancer Health Inequities? - Freudenberger, Devon C.; Deng, Xiaoyan; Vudatha, Vignesh; Riner, Andrea N.; Herremans, Kelly M.; Bandyopadhyay, Dipankar; Fernandez, Leopoldo J.; Trevino, Jose G. (Frontiers in Oncology, 2022)
Background: Advanced cancer states perpetuate health-related disparities. Peritoneal-based cancers are clinically advanced cancers that present a significant clinical dilemma. Peritoneal cancers are managed aggressively with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). While racial and ethnic disparities are prevalent in cancer, there are no studies investigating if racial disparities exist in patients with peritoneal carcinomatosis managed with CRS and HIPEC. We hypothesized that this advanced disease state further delineates racial disparities. Methods: A retrospective chart review was conducted on patients with peritoneal carcinomatosis receiving CRS and HIPEC at a single institution from January 1, 2017-October 4, 2021. Descriptive statistics were used to compare racial groups. The Cox Proportional Hazards Model and Log Rank Test were used for multivariate and overall survival analysis. Results: In total, 67 patients underwent CRS and HIPEC, of which 41 (61.2%) were White, 20 (29.8%) were Black, 3 (4.5%) were Asian, and 3 (4.5%) were Other race. When compared to White patients, Black patients had lower income (p=0.0011), higher incidence of hypertension (p=0.0231), and lower performance status (p=0.0441). Cancer type, including colorectal, appendiceal, ovarian, etc., was similar between groups (p=0.8703). Despite these differences in sociodemographic and morbidity factors, when comparing Black patients to White patients, there were no differences in peritoneal cancer index score (13.2 vs. 12.3, p=0.6932), estimated blood loss (748 vs. 655 mL, p=0.6332), minor/major complication rates (1.1 vs. 1.2, p=0.7281; 0.4 vs. 0.7, p=0.3470, respectively), 30-day readmission rates (25.0% vs. 17.1%, p=0.6210), disease recurrence (40.0% vs. 51.2%, p=0.3667), or 30-day mortality (0.0% vs. 2.4%, p=1.0000). Overall survival was similar for Black and White patients (p=0.2693). The occurrence of a major complication was the only factor associated with overall survival (HR 2.188 [1.502, 3.188], p< 0.0001). Conclusions: Despite differences in patient socioeconomic factors and comorbid conditions, outcomes were similar between Black and White patients receiving CRS and HIPEC at our institution. While larger studies with more diverse patient populations are needed to confirm these findings, our data provide evidence that aggressive surgical management across diverse patient populations allows for equitable outcomes.